Association Between Airborne Infection Isolation Room Utilization Rates and Healthcare Worker Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infections in 2 Academic Hospitals. (2nd October 2021) - Klompas, Michael; Ye, Shangyuan; Vaidya, Vineeta; Ochoa, Aileen; Baker, Meghan A; Hopcia, Karen; Hashimoto, Dean; Wang, Rui; Rhee, Chanu
Abstract: We compared healthcare worker severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection rates between March and August 2020 in 2 similar hospitals with high vs low airborne infection isolation room utilization rates but otherwise identical infection control policies. We found no difference in healthcare worker infection rates between the 2 hospitals, nor between patient-facing vs non-patient-facing providers.